Comercialización de un sistema administrador de cambios en el desarrollo de aplicaciones informáticas - Aguilar, D. (2010)
efficiently control the developing process. This control will optimize the resources assigned to the projects and minimize systems failures that could affect the operation of the company. Based on that facts, it has been set an excellent opportunity to design, build and market a tool that help companies that develop application software to manage, check and control in a efficient way the changes produced by their software. Using ADCA as a tool to support the change management in application software will meaningfully reduce the risk of unexpected interruptions and will lead the company to a controlled human resource assignment. The support will be help by having gathered all the changes made to the application software in one main repository. In addition, ADCA will help companies to make decisions and to improve their operation by having statistics reports of fulfillment and performance.